(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Mobility is a socioeconomic concept, and the demand for it is only going to grow in importance in the foreseeable future. Clean, cost-effective, and ecologically acceptable modes of transportation should be used wherever possible. Hydrogen is an attractive synthetic energy source for the transportation industry because of its high gravimetric energy density and availability in combined form throughout the world. In contrast, its oxidation component somehow doesn’t contribute to greenhouse emissions, enabling it a potential replacement to fossil fuels. Its economically practical electricity generated by sustainable resources, on-board collection to give a required driving range, employment of long-lasting types of energy, and the construction of infrastructures for its supply continue to be important challenges. Using hydrogen energy source presents a variety of environment related implications, which are covered in this article. Recent developments in the manufacturing, transport, administration, and transport of hydrogen also are mentioned. This study finds that nonrenewable sources now dominate hydrogen manufacturing processes; nevertheless, improvements and encouragement of the use of renewable sources for hydrogen production are required in order to make it completely sustainable.